Hubungan Riwayat Berat Badan Lahir (BBL) Dengan Perkembangan Motorik Halus Anak Usia 2-5 Tahun Di Posyandu Gonilan Kartasura - Chapakia, Miss Iman (2016)
Background : The most important phase of children development was age 2-5 where it was a golden period of children development. In Indonesia, between 5-10% of children with delayed of development. Birth weight was one key factor that determine development in children. Low birth Weight associated with delayed development, education, and behavior in the future. Because of that, earlier detection should be held. One of instrument that used to assess the development DDST II (Denver Development Screening Test II). Objectives : To analyze Correlation between birth weight with fine motoric development of children age 2-5 in Posyandu Gonilan Kartasura. Methods : This study used an analytical observational study with case control retrospective design. The samples in this study were chosen by purposive sampling. Assessment of development as a primary data was conducted by Denver II test on 60 samples of children age 2-5 according to inclusion criteria. Data analyzed using Chi Square. Results : Based on bivariate analysis with Chi square obtain there is correlation between birth weight with fine motoric development of children age 2-5 in Posyandu Gonilan Kartasura, p = 0.02 and OR = 5.0 Conclusion : There is correlation between birth weight with development of fine motoric, where is baby with lower birth weight become a risk factor of distracted fine motoric development.